The Level of Achieving Intermediate Stage Curricula the National-Transformation Program 2020 Goals from the point of view of teachers in the schools of the West Riyadh Office for Boys - Alsomaie, Bandar Mohammd; Albdour, Ahmed Hasan (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the level of achievement of the intermediate school curricula for the objectives of the national transformation program 2020 from the intermediate school teachers point of view in the schools of the West Riyadh Office for Boys , and to reveal the statistically significant differences between the means of teachers' responses on achieving the objectives of the intermediate school curricula to the strategic objectives of the National Transformation Program 2020 according to:(academic specialization, scientific qualification, number of years of teaching experience). To achieve the objectives of the research, the research used the descriptive approach in the survey method, and the questionnaire was adopted as a tool for data collection, and the questionnaire was applied to a sample size of 246 teachers, after verifying its stability, validity and suitability for field application, and the results of the research reached the agreement of teachers with an average grade of appreciation at the level of achieving the intermediate school curricula for the objectives of the National Transformation Program 2020, and that the highest levels of achievement of the intermediate school curricula for the goals of the intermediate school. the national transformation program 2020 is represented in the following statements, all of them came with a high appreciation of the three phrases and arranged according to the arithmetic average as follows: The intermediate school curriculum contributes to the availability of learning services to all segments of students, then the intermediate school curriculum enhances the values of students, then the intermediate school curricula enhance the basic skills of students. The lowest levels of achievement of the objectives of the National Transformation Program 2020 are the following statements, all of them came with an average estimate of the three phrases and arranged according to the arithmetic average as follows: the intermediate school curriculum stimulates the educational environment to innovate, the intermediate school curriculum highlights the importance of utilizing water resources, and the intermediate school curriculum encourages volunteering. The results also found that there are statistically significant differences among intermediate school teachers about the achievement of the intermediate school curricula for the objectives of the National Transformation Program 2020 according to the specialization of the academic specialization, and in favor of the computer specialization, and the existence of differences according to the number of years of teaching experience and in favor of the number of years of teaching experience that are less than 5 years, and the results of the research did not reveal statistically significant differences according to the scientific qualification.
Keywords: Vision; Arrival; Courses; Point of View